Teknik Penentuan Status Kesuburan Tanah Eksisting pada Calon Lahan Sawah Bukaan Baru di Sebagian Daerah Irigasi Bulango Ulu Provinsi Gorontalo - nurdin, nurdin (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2023)
In Gorontalo Province, the Bulango Ulu irrigation area (D.I.) has the ability to build new paddy fields, although this potential is unknown, as is the level of soil fertility. The purpose of this study is to identify the variety of soil chemical properties and the level of soil fertility in the area. Three steps make up the soil fertility status technique: collecting soil samples on-site using survey and land observation methods, analyzing soil samples in the lab while examining the variety of soil chemical properties, and calculating soil fertility status using the deskwork methods. With the use of ArcGIS version 10, the analysis's output a spatial map of the distribution of soil fertility status in D.I. Bulango Ulu in Gorontalo Province is provided. The findings indicated that D.I. Bulango Ulu, Gorontalo Province still has a poor diversity of soil chemical properties. The fertility of the local soil is likewise poor.